NARRATIVE REVIEW: POTENSI EKSTRAK BAWANG PUTIH (Allium sativum) DALAM MENINGKATKAN PERTUMBUHAN LACTOBACILLUS DAN MENGHAMBAT BAKTERI PENYEBAB DIARE - Fadillah Amanda; Olyvia Azzahra Putri Hartono; Yusni Atifah (Jurnal Biogenerasi, 2026)
Diarrhea is a global health challenge exacerbated by increasing antibiotic resistance. This narrative review aims to analyze the potential of garlic extract (Allium sativum) as a natural synbiotic agent in supporting Lactobacillus growth while suppressing enteric pathogens. The method used was a narrative review with systematic literature searches through the Google Scholar and PubMed databases. The synthesis results show that garlic contains allicin and fructooligosaccharide (FOS) compounds at 3.34% w/w, which are effective in inhibiting pathogenic bacteria such as Escherichia coli and Salmonella spp., and are able to stimulate the growth of Lactobacillus acidophilus optimally at a concentration of 4%. In conclusion, Allium sativum has dual potential as an antibacterial agent and prebiotic, whose effectiveness is influenced by concentration and extraction method. Further research is needed to standardize the dosage for clinical application.